Intention–Behavior Gap in Post-Return Entrepreneurship of Indonesian Migrant Workers in Japan: A Theory of Planned Behavior (TPB) Approach - Rima Rahayu; Yugo Adil Wicaksono; Samuel Indra Christianto Lumban Tobing; Abdul Rohman (Journal of Business, Social and Technology, 2026)
Background: The increasing migration of Indonesian workers to Japan through two main schemes, namely the Technical Intern Training Program (TITP) and the Specified Skilled Worker Program (SSWP), indicates economic potential for Indonesian Migrant Workers (PMI) after returning to their home country. Objective: This study uses the Theory of Planned Behavior (TPB) to investigate how entrepreneurial attitude, entrepreneurial subjective norm, and perceived behavioral control affect entrepreneurial intention, as well as how entrepreneurial intention affects entrepreneurial behavior. Methods: The research employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) on 307 Indonesian migrant workers who had returned from Japan to Indonesia using purposive sampling. Results: The results show that entrepreneurial attitude is the most important factor determining entrepreneurial intention, followed by perceived behavioral control and entrepreneurial subjective norm. The key link between psychological factors and actual entrepreneurial behavior is entrepreneurial intention, implying that returning migrant workers' transition from attitude development to actual behavior occurs gradually. Conclusion: This study contributes theoretically to understanding the psychological dynamics of post-return entrepreneurship and provides a foundation for developing migrant worker reintegration policies through strengthening entrepreneurial capacity, improving access to financing, and supporting business ecosystems.